Implementation of Machine Learning Using Deep Neural Networks to Estimate the Failure Risk Caused by Leakage in Pressure Relief Devices - Wijayanto, Adi Yudho; Andreano, Yossi; Rizky, M. Ali Yafi; Priadi, Dedi (UI Scholars Hub, 2024)
The primary objective of deploying Pressure Relief Device (PRD) equipment is to ensure the safety of pressure vessels within a pressurized system. Over time, PRD equipment may degrade and fail to perform its intended function, which must be identified as a failure mode. To mitigate potential risks associated with this, it is recommended that an approach such as risk-based inspection (RBI) be implemented. Despite the widespread adoption of RBI, the method relies on qualitative techniques, leading to significant variations in equipment risk assessments. This study proposes a novel risk analysis method that uses deep learning-based machine learning to develop a risk assessment model for PRD equipment related to the fail-on-leakage failure mode. This innovative approach will reduce assessment times, improve accuracy, and lower processing costs by providing precise calculation results. The research develops a risk prediction program that uses deep learning-based machine learning designed explicitly for failure-on-leakage failure mode in pressure relief equipment. The dataset used in the model development process adheres to API 581 standards and comprises 168 data points. Various model parameters are employed, including a test size of 20%, a random state value of 0, 150 epochs, a learning rate of 0.001, and 3 layers with dense values of 128, 64, and 32. The model's performance is evaluated using a validation confusion matrix, which indicates an accuracy of 94%.